In vivo intervertebral disc deformation: intratissue strain patterns within adjacent discs during flexion–extension - Wilson, Robert L. (Sci Rep, 2021)
The biomechanical function of the intervertebral disc (IVD) is a critical indicator of tissue health and pathology. The mechanical responses (displacements, strain) of the IVD to physiologic movement can be spatially complex and depend on tissue architecture, consisting of distinct compositional regions and integrity; however, IVD biomechanics are predominately uncharacterized in vivo. Here, we measured voxel-level displacement and strain patterns in adjacent IVDs in vivo by coupling magnetic resonance imaging (MRI) with cyclic motion of the cervical spine. Across adjacent disc segments, cervical flexion–extension of 10° resulted in first principal and maximum shear strains approaching 10%. Intratissue spatial analysis of the cervical IVDs, not possible with conventional techniques, revealed elevated maximum shear strains located in the posterior disc (nucleus pulposus) regions. IVD structure, based on relaxometric patterns of T(2) and T(1ρ) images, did not correlate spatially with functional metrics of strain. Our approach enables a comprehensive IVD biomechanical analysis of voxel-level, intratissue strain patterns in adjacent discs in vivo, which are largely independent of MRI relaxometry. The spatial mapping of IVD biomechanics in vivo provides a functional assessment of adjacent IVDs in subjects, and provides foundational biomarkers for elastography, differentiation of disease state, and evaluation of treatment efficacy.